Physiotherapy services required at primary health care level in gauteng and limpopo provinces (service provider's perspective -physiotherapists/assistants) - Douglas Maleka; D. Franzsen; A. Stewart (AOSIS, 2008)
This study was conducted to determine the opinion of physiotherapists and physiotherapy assistants with regards to physiotherapyservices required at a Primary Health Care (PHC) level in two provinces ofSouth Africa, one being urban (Gauteng) and the other one more rural(Limpopo). Using a descriptive study design, a sample consisting of 728 physio-therapists and assistants was selected from the HPCSA register list. Datacollection was by a self-administered questionnaire. Sixty six percent of physiotherapists in Gauteng Province and 68% inLimpopo Province agreed that promotive services are required whereas thepercentage for physiotherapy assistants in Gauteng province and Limpopoprovince were 78% and 89% respectively. Preventative services were suggested by 82% and 85% by physiotherapistsand 95% and 96% by physiotherapy assistants in Gauteng and Limpopo. Eighty nine percent and 88% of physio-therapists, 80% and 85% of physiotherapy assistants in Gauteng and Limpopo respectively agreed that curative services are required.  Rehabilitative services were suggested to be required by 83% and 90% of physiotherapists, 85% and 95% by physiotherapy assistants in Gauteng and Limpopo respectively.